Efficacy of motesanib diphosphate in non-small-cell lung cancer. (August 2014) - Rijavec, Erika; Genova, Carlo; Barletta, Giulia; Biello, Federica; Dal Bello, Maria Giovanna; Coco, Simona; Truini, Anna; Vanni, Irene; Alama, Angela; Boccardo, Francesco; Grossi, Francesco
<x xml:space="preserve">Abstract</x> Introduction: Angiogenesis plays a crucial role in the proliferation and in the metastatic spread of tumour cells. Several agents with anti-angiogenic activity have been tested in advanced non-small-cell lung cancer (NSCLC) patients. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Motesanib&logicalOpe1=OR&field2=articletitle&text2=Motesanib&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Motesanib (AMG 706) is a promising anti-angiogenic multi-targeted tyrosine kinase inhibitor (TKI), which has been investigated as a monotherapy or in combination with chemotherapy, in several types of cancer. Areas covered: We have reviewed the literature, and we have presented the results of clinical trials that have investigated the administration of motesanib in advanced NSCLC patients. Expert opinion: Encouraging results have been described with the administration of motesanib as first-line treatment in combination with carboplatin and paclitaxel in Asian patients with non-squamous advanced NSCLC. Further studies are needed in order to identify the predictive biomarkers of response and to select patients who may benefit from this anti-angiogenic treatment.